Analisis kesalahan penggunaan ejaan bahasa Indonesia pada teks karangan narasi peserta didik kelas v SD - Joko Edy Prayitno; Rukayah Rukayah; Joko Daryanto (Universitas Sebelas Maret, 2021)
This study aims to describe: (1) the form of the error, (2) the cause of the error, and (3) the teacher's efforts to overcome the misuse of Indonesian spelling in the essays of fifth grade students of SD Negeri Bumi 1. 67 Surakarta. This research is a qualitative descriptive study with a sample of students' narrative essays. The sampling technique used purposive sampling. Data collection techniques using document analysis and interviews. The data validity test used theory and source triangulation techniques, and referred to PUEBI and KBBI. The data analysis technique uses interactive analysis which includes four stages, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. Percentage of errors in using letters (39.04%), writing words (44.52%), using punctuation marks (10.52%), and writing absorption elements (5.48%). The causes of misuse of Indonesian spelling in student essays include: (1) students do not understand spelling rules and are not aware of mistakes in writing, (2) teachers have not implemented certain strategies, models, or media. The teacher's effort to overcome this is by providing direct corrections and providing training to students to become accustomed to writing.